Improving the Quality of Internships Through Industry Partnerships for Students of the Department of Building Engineering Education - Sitompul, Harun; Matondang, Zulkifli (Jurnal Ilmiah Peuradeun, 2023)
Industrial internship activities prepare students to anticipate various problems in the industrial world and anticipate termination of employment. This study aimed to determine the quality of implementing internships at the Department of Building Engineering Education at Medan State University. The research subjects were Unimed building engineering students who had carried out internships with as many as 43 people. Data collection techniques were carried out using questionnaires and analysis of internship reports. The data analysis technique was carried out descriptively. The study results showed that implementing quality internships can improve students' competencies and attitudes toward the world of work. Based on the results of the research, the implementation of the internship had to be improved: 1) the implementation of the internship should be carried out during college holidays to make it more efficient, 2) the internship report was determined during guidance with students, 3) the internship assessment system was based on reports and student study mastery during the internship, and 4) The competencies obtained during the internship were relatively under several competency achievements in the course. Implementing apprenticeships in the Department of Building Engineering Education still needs attention to prepare more competent graduates.